The role of triglyceride-glucose index in the progression of cardiovascular-kidney-metabolic syndrome: findings from the China health and retirement longitudinal study - Xingyu Zhou; Xingyu Zhou; Yisi Liu; Yisi Liu; Yisi Liu; Yisi Liu; Jiafei Peng; Jiafei Peng; Jiafei Peng; Jiafei Peng; Xianliang Zhou; Hongtao Wei; et al. (Frontiers in Cardiovascular Medicine)
BackgroundCardiovascular-kidney-metabolic (CKM) syndrome is highly prevalent among adults and contributes substantially to cardiovascular morbidity and mortality. However, strategies for its early identification and prevention remain inadequately defined. The triglyceride-glucose (TyG) index, a surrogate marker of insulin resistance, may be associated with CKM progression, but its role across diverse populations and CKM progression patterns warrants further investigation.MethodsA total of 6,311 participants from the China Health and Retirement Longitudinal Study (CHARLS) were included. Associations between the TyG index and CKM progression were assessed using Cox proportional hazards and restricted cubic spline models. Subgroup analyses were conducted by age (<65 vs. ≥65 years), sex, and baseline CKM stage. CKM progression was further categorized to explore associations with specific metabolic outcomes.ResultsAmong 6,311 participants (mean age 57.8 years, 46.3% male), 31.3% experienced CKM progression over a median follow-up of 48 months. The TyG index was significantly associated with CKM progression in individuals aged ≥65 years, with a notable interaction between age and TyG (P for interaction <0.001). In participants with baseline CKM stage 0 or 1, higher TyG levels predicted greater CKM progression risk. A U-shaped relationship was observed in stage 0 (P = 0.018, P for non-linearity = 0.09), whereas a linear positive association was noted in stage 1 (P = 0.002, P for non-linearity = 0.008). Elevated TyG was primarily linked to subsequent hypertriglyceridemia in stage 0 (Q4 vs. Q1: HR 3.13, 95% CI 1.65–5.91, P < 0.001) and to future diabetes (Q4 vs. Q1: HR 2.85, 95% CI 1.56–5.22, P < 0.01), metabolic syndrome (Q4 vs. Q1: HR 1.62, 95% CI 1.10–2.37, P < 0.05), and hypertriglyceridemia (Q3 vs. Q1: HR 1.63, 95% CI 1.13–2.34, P < 0.01; Q4 vs. Q1: HR 2.21, 95% CI 1.58–3.08, P < 0.01) in stage 1.ConclusionElevated TyG index is a significant predictor of CKM progression, particularly via the development of metabolic abnormalities. Its predictive value varies across age groups and CKM stages. Early screening and intervention targeting TyG levels, especially in older adults and those with early-stage CKM, may be critical for halting CKM progression and reducing future cardiovascular risk.